Comparative Study of multiple Access Methods used forMobile communications - Negrat, Abd Albaset (جامعة مصراتة, 2010)
In this paper, comparative study of multiple Access methods used for mobile systems network has been introduced. First- generation cellular systems are based on analog FM radio technology, with the objective of improving quality and increasing capacity, second - generation cellular systems-based on digital radio technology and advanced networking principles - are deployed world - wide. \ Radio - Access methods determines the quality and network capacity of a system. These second - generation system use either time - division multiple access (TDMA) or code - division multiple access (CDMA) to increase overall system capacity. The third - generation system uses code — division multiple access (CDMA) for better system capacity.
Keywords: الاتصالات السلكية واللاسلكية; تكنولوجيا الاتصالات